Washing away the sins of the past - Goldin, Jaqui (2003)
The National Water Act of 1998 is the legislative framework for integrated catchment management in South Africa. It is a progressive legislation that advocates inclusion and aspires to narrow the gap of unequal access to water in South Africa. The legitimacy and representativity of the catchment management agency depends largely on the success of the process leading to its establishment. The dynamic between the creation of trust and the construction of water management institutions is examined. The article highlights the problems that have emerged in the attempt to reform management systems and concludes that water management bodies need to more assertively build trust and reduce shame relations particularly amongst ordinary water users. - Reproduced.
Keywords: Water law